The ghost of mimicry past: laboratory reconstitution of an extinct butterfly ‘race’ (1997)
Four variable traits that determine mimetic colour patterns in the butterfly, Heliconius cydno, evolved between 1908 and 1984–91. There was a decline in the frequencies of alleles and phenotypes that confer resemblance to the co-mimic, Elzunia humboldt regalis, and an increase in the frequencies of alleles and phenotypes that confer resemblance to the alternative co-mimic, Heliconius erato chestertonii. Elzunia humbolt regalis was formerly common but is now restricted to forest fragments, whereas H. e. chestertonii occurs principally in disturbed habitats, where it is now common. Human disturbance of habitats is thought to have changed the relative abundances of the two co-mimics, and hence the selection operating on H. cydno. The form of H. cydno that is presumed to have been a near-perfect mimic of H. h. regalis is no longer found in the wild: this form would have been homozygous for the rarer alleles at all four loci. It has been possible to reconstruct this form on two occasions in the laboratory, breeding from partially heterozygous wild-caught female butterflies.